Development of English Teaching Materials Based On Minangkabau Tradition in class X SMAN 1 Sungai Puar - Ikhlimah, Ikhlimah; Miboy, Arif; Syahrul, Syahrul (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The aim of this research is to develop English language teaching materials based on Minangkabau tradition in class X of SMAN 1 Sungai Puar. This research design is R & D research, with ADDIE procedure. This research is the X grade students of SMAN 1 Sungai Puar in the 2018/2019 year. The researcher took sample of class X MIPA 1 as an experimental class. There are several instruments in this research, namely interviews, validation sheets, and tests. After that, the initial test and the final test is carried out in class X MIPA 1 as a sample. It was found that English teaching materials based on Minangkabau local wisdom was current teaching materials that never given before in this school. This teaching materials was practical, effective, and improve students' mastery of English.